A Metal Organic Framework Derived Solid Electrolyte for Lithium–Sulfur Batteries. Issue 27 (5th June 2020) - Chiochan, Poramane; Yu, Xingwen; Sawangphruk, Montree; Manthiram, Arumugam
Abstract: Lithium–sulfur batteries (LSBs) are currently considered as promising candidates for next‐generation energy storage technologies. However, their practical application is hindered by the critical issue of the polysulfide‐shuttle. Herein, a metal organic framework (MOF)‐derived solid electrolyte is presented to address it. The MOF solid electrolyte is developed based on a Universitetet i Oslo (UIO) structure. By grafting a lithium sulfonate (‐SO3 Li) group to the UIO ligand, both the ionic conductivity and the polysulfide‐suppression capability of the resulting ‐SO3 Li grafted UIO (UIOSLi) solid electrolyte are greatly improved. After integrating a Li‐based ionic liquid (Li‐IL), lithium bis(trifluoromethanesulfonyl)imide in 1‐ethyl‐3‐methylimidazolium bis(trifluoromethylsulfonyl)imide, the resulting Li‐IL/UIOSLi solid electrolyte exhibits an ionic conductivity of 3.3 × 10 −4 S cm −1 at room temperature. Based on its unique structure, the Li‐IL/UIOSLi solid electrolyte effectively restrains the polysulfide shuttle and suppresses lithium dendritic growth. Lithium–sulfur cells with the Li‐IL/UIOSLi solid electrolyte and a Li2 S6 catholyte show stable cycling performance that preserves 84% of the initial capacity after 250 cycles with a capacity‐fade rate of 0.06% per cycle. Abstract : By grafting a lithium sulfonate (‐SO3 Li) group onto the ligand of Universitetet i Oslo (UIO), the resulting metal organic framework derived solid electrolyte (UIOSLi) shows an acceptable Li + ‐ion conductivity with polysulfide‐suppression capability. Lithium–sulfur cells with the ionic liquid incorporated UIOSLi membrane show remarkably stable cycling performance.